Mechanical Properties and Morphology of Hyperbranched Polyether/HTPB-PU IPN - Song, Xuejing; Luo, Yunjun (Asian Journal of Chemistry, 2013)
In the hope of improving mechanical properties of hydroxyl-terminated polybutadiene-based polyurethane (HTPB-PU), hyperbranched polyether is introduced into HTPB-PU system and form hyperbranched interpenetrating polymer network (H-IPN) through IPN technology. Test of mechanical properties shows that the maximum tensile strength and elongation of hyperbranched polyether/HTPB-PU IPN has been improved more than threefold than those of HTPB-PU. Hydrogen bond and microphase separation between H-IPN are reasons why mechanical properties of H-IPN have been enhanced. As hyperbranched polyether/HTPB-PU IPN has microphase separation, when hyperbranched polyether shows dispersed phase with the grain diameter 0.8 μm around, it has optimal mechanical properties, on opposite when hyperbranched polyether shows continuous phase, mechanical properties of H-IPN is reduced.